Analisis Tingkat Usability dan User Experience LMS Institut Widya Pratama dengan Pendekatan UEQ (User Experience Questionnaire) - Ign.F.Bayu Andoro (Lembaga Pengembangan Kinerja Dosen, 2025)
This study analyzes the usability and user experience (UX) of the Widya Pratama Institute's Learning Management System (LMS) using the User Experience Questionnaire (UEQ). The background of this study is the crucial role of LMS in contemporary education, where this system is the backbone of the online and hybrid learning process. Learning effectiveness is determined not only by the available content, but also by the ease, comfort, and satisfaction of users when accessing and interacting with the system. Therefore, UX quality is an important indicator for assessing the success of an LMS in supporting teaching and learning activities. The main objective of this study is to determine the extent to which the system meets user expectations and identify areas for improvement. The method used involved a survey of 69 students using 26 standard UEQ questions covering six scales: attractiveness, clarity, efficiency, absorption, stimulation, and novelty. The data obtained were tested for validity and reliability, then compared with global UEQ benchmarks to objectively assess the LMS's position. Key findings indicate that the LMS is highly efficient and reliable in terms of technical functionality and accessibility. However, low scores were found for attractiveness, interface brightness, interaction stimulation, and innovation (novelty), which are crucial for shaping positive user perceptions. Lack of visual appeal, limited personalization, and a monotonous experience discourage students from engaging more deeply. These findings highlight the urgent need to update visual elements, increase interactivity, and introduce innovative features that enhance user curiosity and enjoyment. Furthermore, improved documentation and user guides are needed to enable new users to quickly and easily grasp LMS functionality.